Peningkatan Kandungan Nutrisi dan Mutu Biskuit Berbasis Tepung Sorgum Melalui Modifikasi Perendaman dan Fortifikasi Tepung Kedelai - Bahlawan, Zuhriyan Ash Shiddieqy; Megawati, Megawati; Damayanti, Astrilia; Abdurrafi, Faishol; Hutomo, Gayuh Aditya (REACTOR: Journal of Research on Chemistry and Engineering, 2025)
Biscuits are a popular snack due to their practicality, affordability, and potential as a high-nutrition food. However, biscuit production in Indonesia still depends on imported wheat flour, which poses challenges, especially for people with gluten intolerance or wheat allergies. Therefore, the development of local flour alternatives is essential to support food diversification and reduce wheat dependence. Sorghum (Sorghum bicolor (L.) Moench) is a potential local cereal with high carbohydrates and gluten-free properties but contains tannins that can reduce nutritional quality. This study aimed to evaluate the effect of NaOH soaking on reducing tannin content in sorghum flour and its application in biscuit production with soybean flour fortification as a protein source. Sorghum was soaked in NaOH solution (0.1–0.3%) at 30–50°C. Biscuits were formulated with soybean flour substitution levels of 0–50%. The biscuits were analyzed for proximate composition, tannin content, and sensory properties. Data were analyzed using ANOVA test. Results showed that NaOH soaking reduced tannin content up to 72.455 ppm. Soybean flour substitution significantly affected protein, fat, and carbohydrate content (p < 0.05) but not crude fiber. The highest protein content (8.03%) was found in biscuits with 50% soybean flour, while the highest carbohydrate content (64.40%) was in biscuits without soybean flour. Sensory analysis showed no significant difference between biscuit variants (p > 0.05). This study demonstrates the potential of NaOH-modified sorghum flour combined with soybean flour fortification for producing high-nutrition biscuits and supporting local flour diversification in Indonesia.